1983
DOI: 10.1073/pnas.80.19.6126
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies distinguish phosphorylated and nonphosphorylated forms of neurofilaments in situ.

Abstract: The immunocytochemical staining patterns of 37 neuron-specific monoclonal antibodies previously described fell into four groups: (i) anti-synapse-associated, (ii) anti-neurofibrillar, (iii) anti-perikaryonal-neurofibrillar, and (iv).a single antibody reactive with a widely distributed epitope that covered the patterns of groups ii and iii. Antibodies of groups ii, iii, and iv were shown to be specific to neurofilament triplet subunits, even though there was little overlap in staining patterns between groups ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
645
1
7

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 992 publications
(684 citation statements)
references
References 16 publications
(18 reference statements)
31
645
1
7
Order By: Relevance
“…Our data also indicate a proline-directed serine kinase is responsible for generating the mAb SMI-31 epitope on MAP lB. mAb SMI-31 also recognises phosphorylation epitopes on tau and the high and intermediate weight proteins of neurofilaments (Sternberger and Sternberger, 1983;Lichtenberg-Kraag et al, 1992;Ulba et al, 1993) and these epitopes contain serine! proline sites (Lichtenberg-Kraag et al, 1992;Doroudchi and Durham, 1996).…”
Section: Figsupporting
confidence: 58%
“…Our data also indicate a proline-directed serine kinase is responsible for generating the mAb SMI-31 epitope on MAP lB. mAb SMI-31 also recognises phosphorylation epitopes on tau and the high and intermediate weight proteins of neurofilaments (Sternberger and Sternberger, 1983;Lichtenberg-Kraag et al, 1992;Ulba et al, 1993) and these epitopes contain serine! proline sites (Lichtenberg-Kraag et al, 1992;Doroudchi and Durham, 1996).…”
Section: Figsupporting
confidence: 58%
“…Myelination correlates with neurojilament phosphorylation and spacing Previous studies have found low levels of phosphorylated neurofilament immunoreactivity in the perikarya, dendrites, and short initial segments, and usually have found that phosphorylation is high within the axons (Stemberger and Stemberger, 1983;Lee et al, 1986Lee et al, , 1987Oblinger, 1987). Because the initial segment is very short in the neurons, it was not clear whether increased phosphorylation is an intrinsic feature of axon per se, or whether it is influenced by the presence of the myelination.…”
Section: Discussionmentioning
confidence: 99%
“…They did not colocalize with tau filaments (not shown), but neurons with NFTs did show abnormal compartmentalization of neurofilament epitopes. Specifically, there was aberrant phosphorylated neurofilament in neuronal perikarya and non-phosphorylated neurofilaments (Sternberger and Sternberger, 1983). …”
Section: Immunoelectron Microscopy Of Tau or Asn In The Substantia Nigramentioning
confidence: 99%
“…Specifically, there was aberrant phosphorylated neurofilament in neuronal perikarya and non-phosphorylated neurofilaments in myelinated axons (not shown). Non-phosphorylated neurofilaments are usually compartmentalized to neuronal cell bodies and phosphorylated neurofilaments to axons (Sternberger and Sternberger, 1983). …”
Section: Immunoelectron Microscopy Of Tau or Asn In The Substantia Nigramentioning
confidence: 99%